RAD21 Confers Poor Prognosis and Affects Ovarian Cancer Sensitivity to Poly(ADP-Ribose)Polymerase Inhibitors Through DNA Damage Repair - Gou, Rui; Li, Xiao; Dong, Hui; Hu, Yuexin; Liu, Ouxuan; Liu, Juanjuan; Lin, Bei (Frontiers in Oncology, 2022)
Background: Poly (ADP-ribose) polymerase (PARP) inhibitors are a class of molecular targeted cancer drugs. Synthetic lethality is a phenomenon that renders homologous recombination repair defective cells more sensitive to PARP inhibitors. As a component of the cohesin complex, RAD21 regulates DNA damage repair. However, the biological roles of RAD21 in ovarian cancer and their underlying mechanisms remain unclear. Methods: Immunohistochemical assay was used to validate the expression of RAD21 in ovarian cancer and its correlation with prognosis. The effects of RAD21 were evaluated through CCK8, wound healing, and invasion assays in vitro, and the tumor growth in vivo. Furthermore, CCK8 assay and immunofluorescence assay were used to detect the effect of RAD21 on cell sensitivity to PARP inhibitors and its mechanism. The pathway changes were detected by western blot. Results: RAD21 was markedly upregulated in ovarian cancer samples. High RAD21 expression was correlated with poor differentiation and poor prognosis in patients with ovarian cancer. Functionally, RAD21 overexpression promoted cancer cell proliferation, migration, and invasion. Moreover, RAD21 knockdown increased the sensitivity of ovarian cancer cells to three kinds of PARP inhibitors by affecting DNA damage repair. In vivo experiments indicated that RAD21 promoted tumor growth. Mechanistically, the overexpression of RAD21 led to increased phosphorylation levels of Akt and mTOR. Blocking the Akt/mTOR signaling pathway reversed RAD21 overexpression-induced cancer progression and drug resistance. Conclusions: RAD21 can serve as a valuable prognostic marker for ovarian cancer and has potential as a therapeutic target that can expand the utility of PARP inhibitors.